Existence and Simulation of Solutions for a Class of Fractional Differential Systems with $p$-Laplacian Operators on Star Graphs (Journal of Nonlinear Modeling and Analysis, 2025)
This paper is mainly concerned with the existence and simulation of solutions for a class of Caputo fractional differential systems with $p$-Laplacian operators on star graphs. The Hyers-Ulam stability of the systemson star graphs is also proved. Furthermore, an example on a formaldehydegraph is presented to demonstrate the practicality of the main results. Theinnovation of this paper lies in combining a fractional differential system witha formaldehyde graph, interpreting the chemical bonds as the edges of thegraph, and exploring the existence and numerical simulation of solutions tothe fractional differential system on this unique graph structure.
Keywords: Fractional differential systems; $p$-Laplacian operator; star graphs; existence; Hyers-Ulam stability.